The trophic ecology of parrotfish of Zanzibar application of stable isotope analysis,Trophic ecology of parrotfish in Zanzibar : applications of stable isotope analysis - Plass-Johnson, Jeremiah Grahm (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2012)
Parrotfish are a critical component of the herbivore functional group on tropical coral reefs around the world because they mediate competition that occurs between algae and scleractinian corals. Also, because of their feeding technique, which consists of rasping at the substratum with their beak-like teeth, they play an important role in carbonate turnover and the clearing of reef surface area for the settlement of new sessile organisms. Because of these roles, parrotfishes are an important structuring component of coral reef communities. However, individual species can play different roles depending on their physiology, behaviour and ecology. Despite the possible ecological differences that may exist amongst species, specific roles of the fishes remain unclear as the group is most often studied at higher community levels. This thesis applied stable isotope analysis to differing levels of organisation within a parrotfish community to help elucidate their trophic ecology on coral reefs in Zanzibar. Firstly, blood and muscle tissues were compared to identify differences in their isotope signatures. In other organisms, blood turns over faster than muscle tissue so that muscle tissue represents the diet as integrated over a longer period of time. In most species of parrotfish the blood and muscle Î´Â¹Â³C signatures were not found to be significantly different, but the Î´Â¹â µN signatures were significantly different between tissues. This indicated that the Î´Â¹Â³C signature of both tissues would reveal similar dietary information. Conversely, differences in the Î´Â¹â µN signature indicated that the nitrogen relationship between tissues was more complicated. Secondly, spatial variability in parrotfish, coral, detritus and macroalgae isotope signatures was assessed at different scales. In macroalgae and coral tissues (zooxanthellae and polyp treated separately), the Î´Â¹Â³C signatures were shown to differ with depth, presumably because of changes in photosynthetic processes related to depth-associated changes in light. While Î´Â¹â µN signatures were not affected by depth, all organisms showed enrichment at the Nyange reef, the closest reef to the capital of Zanzibar, Stone Town, presumably reflecting the effects of sewage outfall. These results show that processes that impact the Î´Â¹â µN signatures of primary producers (macroalgae and zooxanthellae) can be traced to higher trophic levels (coral polyps and fish). Lastly, Î´Â¹Â³C and Î´Â¹â µN signatures were used to identify ontogenetic dietary changes in multiple species of parrotfish. Four of the species showed stages that varied from the diets that are normally assumed on the basis of their dentition and feeding technique. This indicates that functional roles based on taxonomy or morphology may fail to include possible ontogenetic dietary changes, and may also fail to elucidate the full impact a species could have on coral reef communities. The conclusions from these studies indicate that the species-specific ecological role of parrotfish in coral reef communities can be complex within and between species, and may differ amongst reefs. In light of the natural and anthropogenic pressures that affect coral reef systems, management decisions based on a more complete understanding of the role of these fish in coral reef communities will help decisions that maintain resilience in these fragile systems.
Keywords: Parrotfishes -- Tanzania -- Zanzibar; Parrotfishes; Parrotfishes -- Ecology -- Tanzania -- Zanzibar; Parrotfishes -- Behavior -- Tanzania -- Zanzibar; Parrotfishes -- Food -- Tanzania -- Zanzibar; Scleractinia -- Tanzania -- Zanzibar; Algae -- Tanzania -- Zanzibar; Coral reefs and islands -- Tanzania -- Zanzibar; Coral reef fishes -- Tanzania -- Zanzibar; Stable isotopes